Transient mirror writing in migraine: An uncommon clinical observation (Indian Journal of Case Reports, 2024)
Migraine aura, a transient neurological dysfunction, is characterized by reversible (<60 min) visual, sensory, language, and/or motor symptoms. This case report presents a 19-year-old female patient with frequent migraines who exhibited mirror writing during migraine episodes. Neurological assessments ruled out structural abnormalities, and the mirror writing was consistently observed in conjunction with migraine attacks. This case highlights a potential neurological connection between migraine and atypical manifestations such as mirror writing. The findings suggest that such symptoms may be overlooked in migraine patients, emphasizing the need for increased awareness and further investigation into the diverse presentations of migraines. This report contributes to understanding the complex relationship between migraine and neurological phenomena.